Cyclic AMP-CRP Modulates the Cell Morphology of Klebsiella pneumoniae in High-Glucose Environment - Liu, Long; Li, Feiyu; Xu, Li; Wang, Jingjie; Li, Moran; Yuan, Jie; Wang, Hui; Yang, Ruiping; Li, Bei (Frontiers in Microbiology, 2020)
Bacteria can modify their morphology in response to environmental stimuli for survival or host defense evasion. The rich glucose in vivo or in the Luria-Bertani (LB) medium shortened the cell length of K. pneumoniae. The environmental glucose decreased the levels of cyclic AMP (cAMP) and the transcription of crp, which declined the cAMP-CRP activity. The cell length of crp deletion mutant was significantly shorter than that of the wild type (0.981± 0.057 μm vs. 2.415±0.075 μm, P<0.001). These results indicated that the high environmental glucose alters the bacterial morphology to a round form through regulating the activity of cAMP-CRP complex. Comparative proteomics analysis showed increased expression of 10 proteins involved in cell division or cell wall biosynthesis in the crp deletion strain. Five of them (ompA, tolB, ybgC, ftsI and rcsF) were selected to verify their expression in the high glucose environment, and overexpression of tolB or rcsF shortened the bacterial length similar to that of the crp deletion strain. Electrophoretic mobility shift assay (EMSA) indicated CRP directly negatively regulates the transcription of tolB and rcsF by binding to the promoter regions. This study first proved the role and partial regulation mechanism of CRP in altering cell morphology during infection, and provided a theoretical basis for elucidating the mechanism in diabetes mellitus susceptible to K. pneumoniae.